Bittot Van De Longas' Indiscriminate as a Message of Angkola Culture - Amri, Yusni Khairul; Syahputri, Diani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Folklore based on local culture has a mandate as the author's message to the reader (listener), because it has ethnic sensitivity in understanding local culture as cultural identity. The study uses the opinion of Dundes (1965:2) Bruvand (1965), Danandjaja (1997) and the concept of mandate according to Bascom in Danandjaja (1995:3-20). Miles and Huberman's (2007) qualitative research methodology includes data collection of folklore texts, data presentation, and drawing conclusions or verification. Based on the analysis of folklore data from a book entitled 'Halilian: Turi-turian Hi Halak Sipirok Banggo-banggo' by H. Abdurrahman Ritonga (2006). Folklore has a very strong ethnic bias in folklore which functions to bring closer to indigenous peoples who are rooted in characters. The mandate in the Sipirok folklore is a message based on the knowledge of the author who wants to be conveyed to others through the intermediary of the story said or composed. Through the stories, attitudes and behavior of the characters, readers are expected to be able to take lessons from the messages conveyed and mandated by the mandate as messages conveyed by the author through the behavior of folklore characters essentially, messages that educate readers. The message contained in the Sipirok folklore text as essential in educating Based on the folklore data entitled Anthology Book: 'Halilian: Turi-turian ni Halak Sipirok Banggo-banggo which has the form: Bittot Van De Longas, the results of the analysis of the text found the following messages: a ) mandate to love each other, b) mandate to live a life of concern for lack, c) mandate to empathize, d) befall (unfortunate fate of characters), e) mandate to be humble, f) mandate to work hard, g) to (not) be wise in the story message the people of Angkola.